2015
DOI: 10.1681/asn.2015060688
|View full text |Cite
|
Sign up to set email alerts
|

Past Decline Versus Current eGFR and Subsequent Mortality Risk

Abstract: A single determination of eGFR associates with subsequent mortality risk. Prior decline in eGFR indicates loss of kidney function, but the relationship to mortality risk is uncertain. We conducted an individual-level meta-analysis of the risk of mortality associated with antecedent eGFR slope, adjusting for established risk factors, including last eGFR, among 1.2 million subjects from 12 CKD and 22 other cohorts within the CKD Prognosis Consortium. Over a 3-year antecedent period, 12% of participants in the CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 36 publications
4
53
0
2
Order By: Relevance
“…Our findings show higher risk of poor outcomes for moderately to severely reduced eGFR but lower risk for mildly and mild to moderately decreased eGFR. Similar findings have been observed previously in general population cohorts [15,16]. These findings are probably due to the severity of illness of patients in the eGFR category of ≥90 ml/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings show higher risk of poor outcomes for moderately to severely reduced eGFR but lower risk for mildly and mild to moderately decreased eGFR. Similar findings have been observed previously in general population cohorts [15,16]. These findings are probably due to the severity of illness of patients in the eGFR category of ≥90 ml/min/1.73 m 2 .…”
Section: Discussionsupporting
confidence: 91%
“…Causes of increased risk for poor prognosis with increase in eGFR during hospital stay are unclear. It is possible that an increase in eGFR during hospital stay may not indicate true improvement in kidney function but may indicate deterioration of physical condition which may have resulted in overestimation of kidney function at the second measurement closer to discharge .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported significant associations between a rise in eGFR and mortality risk. 1014 In the CKD Prognosis Consortium, a eGFR cr slope of +6 mL/min/1.73 m 2 per year was associated with 1.58 (95% CI, 1.29–1.95) times higher risk of all-cause mortality in a meta-analysis of CKD cohorts. 14 We would expect an increase in mGFR to be associated with better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1014 In the CKD Prognosis Consortium, a eGFR cr slope of +6 mL/min/1.73 m 2 per year was associated with 1.58 (95% CI, 1.29–1.95) times higher risk of all-cause mortality in a meta-analysis of CKD cohorts. 14 We would expect an increase in mGFR to be associated with better health outcomes. Alternatively, a rise in mGFR might reflect glomerular hyperfiltration or recovery from an acute kidney injury episode, which may be associated with adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation